2021
DOI: 10.1002/adhm.202001853
|View full text |Cite
|
Sign up to set email alerts
|

Combinatory Delivery of Etoposide and siCD47 in a Lipid Polymer Hybrid Delays Lung Tumor Growth in an Experimental Melanoma Lung Metastatic Model

Abstract: This study investigated the feasibility of lipid polymer hybrid nanoparticles (LPH) as a platform for the combinatorial delivery of small interfering RNA (siRNA) and etoposide (Eto). Different Eto loaded LPH formulations (LPH Eto) are prepared. The optimized cationic LPH Eto with a particle size of 109.66 ± 5.17 nm and Eto entrapment efficiency (EE %) of 80.33 ± 2.55 is used to incorporate siRNA targeting CD47 (siCD47), a do not eat me marker on the surface of cancer cells. The siRNA‐encapsulating LPH (LPH siN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 70 publications
0
32
0
Order By: Relevance
“…Others used different types of LNPs conjugated with CD47_siRNA in lung and colon cancers. These studies reported knockdown efficiency values of CD47 between 65 and 80%. , The cytotoxicity of LNPs used here was studied on all cell lines. Results showed high viability (more than 90%) at the concentration used here in cancer and normal cells (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Others used different types of LNPs conjugated with CD47_siRNA in lung and colon cancers. These studies reported knockdown efficiency values of CD47 between 65 and 80%. , The cytotoxicity of LNPs used here was studied on all cell lines. Results showed high viability (more than 90%) at the concentration used here in cancer and normal cells (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Different LPH NPs formulations co-loaded with azithromycin and piroxicam (LPH Azi–Pir ) or niclosamide and piroxicam (LPH Nic–Pir ) were prepared by a single-step nanoprecipitation self-assembly technique. 42 Briefly, PLGA (5 mg mL −1 ), piroxicam (0.75 mg mL −1 ) and azithromycin (0.75 mg mL −1 ) or niclosamide (0.75 mg mL −1 ) were dissolved in DMF (1 mL) to form the organic phase. The aqueous phase was prepared by dissolving lecithin (0.5 mg mL −1 ), DSPE-PEG 2000 (0.5 mg mL −1 ) and Tween® 80 (10 mg mL −1 ) in 4% v/v hydroalcoholic solution (9 mL) at 70 °C for 15 min to ensure the complete desolvation of the lipid.…”
Section: Methodsmentioning
confidence: 99%
“…Al-Jamal and co-workers encapsulated CD47 siRNA and chemotherapeutic drug etoposide in the core of PLGA, and lipids such as lecithin encapsulated it to form LPH, which can protect siRNA from serum and RNase degradation. Meanwhile, the expression of CD47 in melanoma B16 cells was reduced by 50–60%, and the lung metastasis was significantly inhibited in vivo . In summary, with the use of lipids or polymers to protect nucleic acid drugs and the use of the EPR effect of the carrier to penetrate into tumor tissue, the internalized siRNA can effectively reduce the expression of CD47 in tumor cells and inhibit tumor progression.…”
Section: Therapy Strategies Targeted On the Cd47-sirpα Axismentioning
confidence: 98%
“…Meanwhile, the expression of CD47 in melanoma B16 cells was reduced by 50−60%, and the lung metastasis was significantly inhibited in vivo. 121 In summary, with the use of lipids or polymers to protect nucleic acid drugs and the use of the EPR effect of the carrier to penetrate into tumor tissue, the internalized siRNA can 122 To further improve the targeting of these vectors and reduce "off-tumor" effects, aCD47 is used to promote the delivery of nanoparticles and also exert antitumor function or tumor imaging.…”
Section: Antibody and Fusion Proteinmentioning
confidence: 99%